Weibel-Palade Body Localized Syntaxin-3 Modulates Von Willebrand Factor Secretion From Endothelial Cells. Issue 7 (July 2018) - Schillemans, Maaike; Karampini, Ellie; van den Eshof, Bart L.; Gangaev, Anastasia; Hofman, Menno; van Breevoort, Dorothee; Meems, Henriët; Janssen, Hans; Mulder, Aat A.; Jost, Carolina R.; Escher, Johanna C.; Adam, Rüdiger; et al.
Abstract : Objective—: Endothelial cells store VWF (von Willebrand factor) in rod-shaped secretory organelles, called Weibel-Palade bodies (WPBs). WPB exocytosis is coordinated by a complex network of Rab GTPases, Rab effectors, and SNARE (soluble NSF attachment protein receptor) proteins. We have previously identified STXBP1 as the link between the Rab27A-Slp4-a complex on WPBs and the SNARE proteins syntaxin-2 and -3. In this study, we investigate the function of syntaxin-3 in VWF secretion. Approach and Results—: In human umbilical vein endothelial cells and in blood outgrowth endothelial cells (BOECs) from healthy controls, endogenous syntaxin-3 immunolocalized to WPBs. A detailed analysis of BOECs isolated from a patient with variant microvillus inclusion disease, carrying a homozygous mutation in STX3 (STX3 −/− ), showed a loss of syntaxin-3 protein and absence of WPB-associated syntaxin-3 immunoreactivity. Ultrastructural analysis revealed no detectable differences in morphology or prevalence of immature or mature WPBs in control versus STX3 −/− BOECs. VWF multimer analysis showed normal patterns in plasma of the microvillus inclusion disease patient, and media from STX3 −/− BOECs, together indicating WPB formation and maturation are unaffected by absence of syntaxin-3. However, a defect in basal as well as Ca 2+ - and cAMP-mediated VWF secretion was found in the STX3 −/− BOECs. We also show that syntaxin-3 interacts with the WPB-associated SNARE protein VAMP8 (vesicle-associated membrane protein-8). Conclusions—: Our data reveal syntaxin-3 as a novel WPB-associated SNARE protein that controls WPB exocytosis. Abstract : Supplemental Digital Content is available in the text.